Analysis Of Pratama Hospital Health Promotion Implementation Strategies North Nias District - Bulolo, Septalia (TOUR HEALTH JOURNAL, 2023)
Background: Based on (Permenkes RI No. 004, 2012) concerning Technical Guidelines for Hospital Health Promotion, it states that, Hospital Health Promotion (HHP) is a hospital effort to improve the capabilities of patients, clients and community groups, so that patients can be independent in accelerating healing and rehabilitation. A number of programs under the auspices of the HHP program have been implemented, for example advocacy, developing a program for HHP, and carrying out outreach about the HHP program to directors of Government Hospitals. The aim of Hospital Health Promotion is to create a hospital community that is able to implement Clean and Healthy Living Behavior through changing the knowledge, attitudes and behavior of hospital patients as well as maintaining the hospital environment and being able to take advantage of all the services provided by the hospital properly. Purpose: The focus of this research is the strategy for implementing Health Promotion at the Pratama Hospital of North Nias Regency. Method: In this research, researchers used a qualitative descriptive method with a phenomenological study approach aimed at digging deeper into the implementation of the HHP strategy. This research was conducted at the Pratama Hospital of North Nias Regency. The informants in this study were 6 people, namely 4 people from hospital employees, and 2 people from Pratama Hospital patients. In this research, researchers used in-depth interview methods conducted with informants to assist researchers in collecting accurate and effective data. Results: Based on the description of the research results and discussions that have been carried out, the researchers can draw the following conclusions: the implementation of the HHP strategy at Pratama Hospital has not been optimal due to obstacles in understanding with patients in its implementation, less conducive use of the waiting room, one of the places where HHP is implemented and a lack of friendliness. and politeness of staff in serving patients. Disscusion and Conclusion: It is recommended to increase the implementation of advocacy strategies, building atmosphere, community empowerment and HHP partnerships